Masked face recognition - Sim, Song Qin (Nanyang Technological University, 2021)
Biometric security is a type of security that verifies people's physical or behavioural features to identify them. One of them being face recognition, which is a technology that is capable of matching human faces to a database of faces. There are several existing deep learning models used for face recognition. In this project, we are going to develop an alternative approach to this task. We will build our model based on a state-of-the-art model, and apply the attention mechanism. The accuracy of our model will be compared with existing face recognition models to evaluate its effectiveness.